Increased TPSAB1 Copy Number in a Family With Elevated Basal Serum Levels of Tryptase - Hernández-Hernández, Laura; Sanz, Catalina; Marcos-Vadillo, Elena; García-Sánchez, Asunción; Moreno, Esther; Lorente, Félix; González-de-Olano, David; Dávila, Ignacio; Isidoro-García, María (Frontiers in Medicine, 2021)
Background: Some recent familial studies have described a pattern of autosomal dominant inheritance for increased basal serum tryptase (BST), but no correlation with mRNA expression and gene dose have been reported. Objective: We analyzed TPSAB1 mRNA expression and gene dose in a four-member family with high BST and in two control subjects. Methods: Blood samples were collected from the family and control subjects. Complete morphologic, immunophenotypical, and molecular bone marrow mast cell (MC) studies were performed. mRNA gene expression and gene dose were performed in a LightCycler 480 instrument. Genotype and CNV were performed by quantitative real-time digital PCR (qdPCR). Results: CNV analysis revealed a hereditary copy number gain genotype (3β2α) present in all the family members studied. The elevated total BST in the family members correlated with a significant increase in tryptase gene expression and dose. Conclusions and Clinical Relevance: We present a family with hereditary α-tryptasemia and elevated BST which correlated with a high expression of tryptase genes and an increased gene dose. The family members presented with atypical MC-mediator release symptoms or were even asymptomatic. Clinicians should be aware that elevated BST does not always mean an MC disorder.